Critical pedagogy and educational research in the U.S. and Brazil:: an international teaching-research collaboration (Ensino, Saúde e Ambiente, 2021)
This text presents partial results of an international collaborative project, which has Paulo Freire's philosophy as a pillar. This article is both a descriptive report and also a register of individual and collective questions about the intentions of the project in relation to its outcomes and implications. The project was developed as an international partnership between three researchers from three different universities, Tiradentes University (Aracaju, Brazil), the University of Massachusetts Boston (Massachusetts, USA), and Molloy College (New York, USA). The perspectives of Freire's pistemological curiosity (2019) and critical awareness (1967) provide the foundation for our discussion, as this article aims to present the results of the International Dialogical Seminar as an integral part of the project. The voices of the participants (teachers and students) will be the focus with the intention to weave links between them, shedding light on the results of this collaboration of teaching and research across borders. Our work speaks to the importance of transnational and local dialogic spaces for teaching and researching as we have been doing in this work together. The intersections of our worldviews and lifeworlds enable us to see how much more needs to be done to ferret out social injustice locally and globally, and sometimes in our own practices as researchers and educators. Yet, our work also offers hope and possibility as we see the power of epistemological curiosity and dialogue in bringing about strengthened critical consciousness. Freire's work for and contributions to social change remains current and relevant.